Model Pengelolaan Limbah B3 Berbasis EPI (Environmental Performance Indicator) dengan Perspektif LCA (Life Cycle Assesment) dan PROPER (Penilaian Peringkat Kinerja Perusahaan (Studi Kasus Kabupaten Gresik- Jawa Timur) - Arief, Saiful; Prabowo, Rony (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2024)
Industrial development in Gresik Regency is increasing along with industrial B3 waste generation. This study aims to obtain a model for measuring the criticality value, management, and depreciation of the impact of B3 Waste and ranking the company's environmental performance. This research is descriptive qualitative with EPI, LCA and PROPER methods. To determine the level of criticality of B3 waste, initial identification is carried out with criteria, namely the extent of impact, seriousness of impact, probability of impact, exposure time, laws and regulations, control methods and community image of the company, after that in the technical evaluation of B3 waste treatment by conducting FGD, the average weight score is still below 5 so that it can be assumed that the category of impact on the environment and society is further carried out design and determination of measurement indicators with EPI and EPI Validation with quantitative KEPI, with questionnaires 3 company management who have more than 5 years of experience in the field of Health, Safety, Environment then processed with LCA with the results of data processing in the SimaPro 7.0 program with the Eco-Indicator 99 method which measures 11 impact categories obtained the volume of liquid waste increased twice. The results of EPI weighting are included in LCA with 3 impacts, namely carcinogens, respiratory inorganic and climate change obtained the results of environmental performance assessments that do not meet the proposed improvements to red EPI after that B3, EPI, LCA waste management strategies and PROPER assessments are carried out with SWOT PROPER rack matrix analysts. Keywords: b3, waste, epi, lca , proper